Hubungan Antara Kondisi Lingkungan Dengan Keberadaan Jentik Aedes aegypti Di Home Industry Meubel Kayu Desa Ngasem Kecamatan Batealit Kabupaten Jepara Tahun 2017UL Yogi Catur Putra*), Suharyo*)*) - Yogi Catur Putra; Suharyo suharyo (Dian Nuswantoro Semarang, 2019)
The district of jepara is center of wooden chair industry in indonesia, but Jepara is endemic district of hemorrhagic fever. Environmental condition influence the breeding of Aedes aegypti, foun many place as breed’s mosquito. The purposed of study was to analyze correlation of environmental condition and existence of larvae of Aedes aegypti in home industry wooden chair in Ngasem Village sub-district of Batealit, Jepara district 2017.The study was analytical observastional with cross sectional approach. Study population was home industry of wooden chair in Jepara as 213 home industries with sample was 68 home industries. Sample has chosen with simple random sampling. The Statistical analyze with chi square and fisher exact textResult showed that 113 containers have variety made from wood and no-wood. Obtained 40% HI, 29% CI, and 48% BI, with density figure 6-9 or high density. Significant correlation between pH of container (p = 0,002) with relation of larva Aedes aegypti. And no significant correlation of container type (p = 0,148), container temperature (p = 0,204), container volume (p = 0,175) and air humidity (p = 0,157).Needed active role of observing larvae existing routine in home industry wooden chair, especially by the owner and cadres in village Ngasem so that can reduce the breeding of Aedes aegypti.